The appropriation of prescriptions: the case of the «Shared Support Plan» (Plan de Apoyo Compartido, PAC) in the Chilean scholar system - San Martin, Julia; Veyrunes, Philippe (Swiss Journal of Educational Research, 2018)
This article reports the study of the role of prescription within the knowledge-building process by analyzing the activity of an elementary school teacher during a Spanish class period in a Chilean school. The research focuses on the way the teacher takes ownership of the prescriptions in her daily work. Activity analysis, following the «Course of action» theory (Theureau, 2004), allowed to emphasize the knowledge required in this situation and its relation with prescrip- tions. Results show that the teacher updates the built knowledge throughout her experience without taking into account the prescriptions; this finding questions their actual place in teachers’ daily activities.